How Similar Are European Business Cycles? - Michael Bergman (Lund University, School of Economics and Management, Department of Economics, 2004)
In this paper, we focus on how European economic integration has affected the synchronization and the magnitude of business cycles among participating countries. We measure, based on bandpass filtered data, the characteristics of European business cycles analyzing to what extent they have become more similar over time. We also consider the role of other factors such as differences in fiscal and monetary policy, border effects, and trade intensity. Our main finding is that European business cycles are highly synchronized, although we also find that synchronization was higher during periods with highly flexible exchange rates. In addition we find a positive tradeoff between timing and magnitude such that more synchronization coincides with larger relative magnitude. These results raise concern about the consequences of a common monetary policy within EMU.
Keywords: E32; F15; 330; Business cycles; symmetry and co-movement of cycles; magnitude of cycles; economic integration; monetary union